1989
DOI: 10.1039/c39890000091
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the nucleophilicity of allylsilanes

Abstract: Kinetic investigations on t h e reactivity of allylsilanes (1-0)towards the p-methoxy substituted diphenylcarbenium ion (2) are reported.In spite of the wide use of allylsilanes in organic synthesis,l little quantitative information concerning the activation of C=C x-bonds by allylic silyl groups is available. Competition experiments have shown that the reactivity of the C=C double bond towards the diphenylmethyl cation increases by 30 700 when an allylic hydrogen of propene is replaced by a trimethylsilyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Interestingly, bulkier silanes tend to be more (approximately 5 times) reactive than TMS analogues. [46] After migration, the freshly minted carbocation can then be trapped out to forge a stable carbocyle.…”
Section: Allenylsilanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, bulkier silanes tend to be more (approximately 5 times) reactive than TMS analogues. [46] After migration, the freshly minted carbocation can then be trapped out to forge a stable carbocyle.…”
Section: Allenylsilanesmentioning
confidence: 99%
“…This stipulation is known to occur when the silicon atom bears bulky substituents because nucleophilic addition to silicon (and hence desilylation) is retarded (Figure 7). Interestingly, bulkier silanes tend to be more (approximately 5 times) reactive than TMS analogues 46. After migration, the freshly minted carbocation can then be trapped out to forge a stable carbocyle.…”
Section: Allenylsilanesmentioning
confidence: 99%
“…[32,34] constants for the reactions of carbocations with solvents from the ratio of azide-trapped products to solvolysis products (R-N 3 /R-OSolv). [40][41][42] In the late 1980s and early 1990s, the senior author reported a general method to determine rate constants for the reactions of carbocations with p-systems (e.g., alkenes and allyl silanes), [43][44][45][46][47] and it was found that Ritchies constant selectivity relationship [Eq. (1)] was not sufficient to describe the whole body of data.…”
Section: Experimental Factsmentioning
confidence: 99%
“…This value is smaller than any bond angle measured in the other seven‐membered‐ring trans‐ alkenes, and is likely due to hyperconjugative interactions between the σ Si1C1 bond and the π‐system 19. The hyperconjugation and distortion indicate that the CC double bond should be particularly nucleophilic,20 even though the silyl group has an electron‐withdrawing oxygen atom 21. The donating ability of the σ Si1C1 bond would also stabilize a carbocation at the β position (C2) significantly (Figure 4 b).…”
Section: Methodsmentioning
confidence: 71%